Frontispiece: Thermally Tunable Hydrogels Displaying Angle‐Independent Structural Colors. Issue 51 (14th December 2015) - Ohtsuka, Yumiko; Seki, Takahiro; Takeoka, Yukikazu
Abstract : Angle‐Independent Structural Color In their Communication onpage 15368 ff., Y. Takeoka et al. report on thermally tunable hydrogels displaying angle‐independent structural colors that were prepared from colloidal amorphous array templates and carbon black.